Citizenship Preferences of Turkish Parents Regarding Their Children (In Factis Pax: Journal of Peace Education and Social Justice, 2014)
Citizenship is an issue which was discussed by Plato and Aristotle. But from the beginning of the 21st century in particular, in connection with changes in social, cultural and political areas, the number of both national and international studies on citizenship has increased rapidly (Beiner 1999), Caymaz, Ersoy, Kadioglu, Kymlicka, Marshal, Osler & Starkey, Soysal, Ustel.  Also, in some countries specific organizations related to the concept of “the citizen” have been founded and these groups have prepared reports on national and international levels (Qualification and Curriculum Authority, 1998), Council of Europe, Torney-Purta, Lehmann, Oswald & Schulz. In these studies and reports the concept of citizenship has beenhandled and defined differently. The concept of citizenship can simply be defined as legal status of the individual granted by a state or a people.  According to Pierson, citizenship is a positive legal status related to a number of rights and duties, which themselves have been shaped differently in different historical and national contexts.Note: The study was presented at the International Social Studies Symposium (2014), Gazi University, Ankara, Turkey.